Analisis Pengaruh Limbah Cair Terhadap Kualitas Perairan Pantai Kelapa Lima Kota Kupang - Sabuin, Etty; Risamasu, Fonny; Kiaduan, Frans (Bumi Lestari, 2019)
Marine life and natural scenery - in the category of nautical tourism - are the potentials of the Kelapa Lima, Kupang beach. However, there are problems that; construction progress, residentials and bussines activities nearby coast of Kelapa Lima, Kupang, indicated that there are contamination by wastewater into the waters of this beach. Then, this issue is adjusted to the standards Environment Minister Regulation number 51 of 2014 and in 2013 number 115 on the sea water quality standard. The method used is the equation written by Sumiotomo and Nerow (1970) in the Minister of Environment No. 115 of 2003. The formula that is used to calculate the results of studies measuring the location parameter with the default value determined by the Ministry of Environment in 2004. Later, research shows that the quality of the waters of the Pantai Kelapa Lima Kupang has begun to decline in the presence of contamination by sewage. Liquid waste is already affecting marine life that corals and mangroves, while the beauty of the sea coast, the liquid waste is already reducing the amount of oxygen for the oxidation process that takes coastal sea to the decomposition of waste into the sea, causing sedimentation affect water clarity sea shore. Therefore, there needs to be immediate action from the government to educate more people about the importance of maintaining the beauty of the beach, and helped make the disposal of liquid waste discharges in coastal areas to reduce the causes of liquid wastes into the coastal sea.